2020
DOI: 10.1111/imj.14411
|View full text |Cite
|
Sign up to set email alerts
|

Taking the pulse of Timor‐Leste’s cardiac needs: a 10‐year descriptive time‐trend analysis

Abstract: At the time of Indonesian withdrawal in 1999, there were only twenty general doctors for a population of seven hundred thousand (2). By comparison, in Australia at the same time there were 1,787 doctors per seven hundred thousand people (3). In Timor-Leste today, the density of skilled health professionals -1.3 per 1000 population -remains well below the World Health Organisation's recommended lower threshold of 2.3 per 1000 population, and far below Australia's current density of 16.2 health-workers per 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Approximately 300 patients were seen at each clinic over several days, with each patient receiving an interpreter‐guided history, physical examination and focussed echocardiogram performed by Australian cardiologists. The clinics comprise patients invited for review, new referrals from local healthcare facilities and walk‐in patients with self‐reported cardiac symptoms 1 . Data from the February 2019 (face‐to‐face) clinic was extracted for comparison with the online clinics.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 300 patients were seen at each clinic over several days, with each patient receiving an interpreter‐guided history, physical examination and focussed echocardiogram performed by Australian cardiologists. The clinics comprise patients invited for review, new referrals from local healthcare facilities and walk‐in patients with self‐reported cardiac symptoms 1 . Data from the February 2019 (face‐to‐face) clinic was extracted for comparison with the online clinics.…”
Section: Methodsmentioning
confidence: 99%
“…The clinics comprise patients invited for review, new referrals from local healthcare facilities and walk-in patients with self-reported cardiac symptoms. 1 Data from the February 2019 (faceto-face) clinic was extracted for comparison with the online clinics. Parameters included number of attendees, city/town of residence and rates of attendance of patients invited for review.…”
Section: Design Of Face-to-face Clinics Before Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of rheumatic heart disease in Timor‐Leste, a lower middle income country of about 1.3 million people and one hour from Australia, is among the highest in the world 1 . The East Timor Hearts Fund (ETHF; https://easttimorheartsfund.org.au) is the primary facilitator of access to cardiac procedures for people in Timor‐Leste 2 . At the start of the coronavirus disease 2019 (COVID‐19) pandemic, both Australia and Timor‐Leste closed their international borders, and no Timorese patients have undergone cardiac surgery in Australia since March 2020.…”
mentioning
confidence: 99%